Pseudomembranous Colitis: An Update - Harpreet S Brar; Christina M Surawicz (Canadian Journal of Gastroenterology)
Clostridium difficile is the most common nosocomial infection of the gastrointestinal tract. Most cases are associated with antibiotic therapy that alters the fecal flora, allowing overgrowth of C difficile with production of its toxins. Diagnosis is made by detection of the organism or toxin in the stools. A variety of different tests can be used, but none is perfect. A stool culture can be positive in someone without diarrhea, ie, a carrier. While the cytotoxin is the gold standard, it is expensive, and there is a delay before results are available. Thus, many laboratories use the enzyme-linked immunoassay tests to detect toxin of C difficile because they are a more rapid screen. Depending on the specific test used, they can detect toxin A, toxin B or occasionally both. Sensitivity and specificity rates vary. First line therapy for C difficile disease should be metronidazole 250 mg qid for 10 days. Vancomycin should be reserved for severe cases where metronidazole has failed or where metronidazole cannot be tolerated or is contraindicated. Recurrent C difficile disease is a particularly vexing clinical problem. A variety of biotherapeutic approaches have been used. Retreatment with antibiotics is almost always necessary. In addition, the nonpathogenic yeast Saccharomyces boulardii has been showed to be of benefit as an adjunct in preventing further recurrences.